background image

19.8. FUNCOIDAL PRODUCT OF ELEMENTS

300

If

x

u

d

dom

S

6

=

A

then

(

A

,

B

)

S

: (

x

u A 6

=

A

A ×

FCD

B

x

=

B

);

A ×

FCD

B

x

(

A

,

B

)

S

)

= im

S

;

if

x

u

d

dom

S

=

A

then

(

A

,

B

)

S

: (

x

u A

=

A

A ×

FCD

B

x

=

B

);

A ×

FCD

B

x

(

A

,

B

)

S

)

3 ⊥

B

.

So

*

l

(

A

,

B

)

S

(

A ×

FCD

B

)

+

x

=

(

d

im

S

if

x

u

d

dom

S

6

=

A

;

B

if

x

u

d

dom

S

=

A

.

From this by theorem

1546

the statement of our theorem follows.

Corollary

1564

.

Let

A

and

B

be posets of filters over boolean lattices.

For every

A

0

,

A

1

A

and

B

0

,

B

1

B

(

A

0

×

FCD

B

0

)

u

(

A

1

×

FCD

B

1

) = (

A

0

u A

1

)

×

FCD

(

B

0

u B

1

)

.

Proof.

(

A

0

×

FCD

B

0

)

u

(

A

1

×

FCD

B

1

) =

d

{A

0

×

FCD

B

0

,

A

1

×

FCD

B

1

}

what is

by the last theorem equal to (

A

0

u A

1

)

×

FCD

(

B

0

u B

1

).

Theorem

1565

.

Let (

A

,

Z

0

) and (

B

,

Z

1

) be primary filtrators over boolean

lattices. If

A ∈

A

then

FCD

is a complete homomorphism from the lattice

A

to

the lattice

pFCD

(

A

,

B

), if also

A 6

=

A

then it is an order embedding.

Proof.

Let

S

P

A

,

X

Z

0

,

x

atoms

A

.

D

l

FCD

S

E

X

=

l

B∈

S

A ×

FCD

B

X

=

(

d

S

if

X

u

A

A 6

=

A

B

if

X

u

A

A

=

A

=

D

A ×

FCD

l

S

E

X.

Thus

d

FCD

S

=

A ×

FCD

d

S

by theorem

1509

.

D

l

FCD

S

E

x

=

l

B∈

S

A ×

FCD

B

x

=

(

d

S

if

X

u

A

A 6

=

A

B

if

X

u

A

A

=

A

=

D

A ×

FCD

l

S

E

x.

Thus

d

FCD

S

=

A ×

FCD

d

S

by theorem

1542

.

If

A 6

=

A

then obviously

A ×

FCD

X v A ×

FCD

Y ⇔ X v Y

, because im(

A ×

FCD

X

) =

X

and im(

A ×

FCD

Y

) =

Y

.